Pollinium development in Spiranthes sinensis (Pers.) Ames.and Cymbidium pendulum SW: a comparative study (Bangladesh Journal of Botany, 2014)
Comparative studies on the early anther development, anther wall differentiation, pollinium development and pollen grains surface features in Spiranthes sinensis (Pers.) Ames. (a terrestrial orchid) and Cymbidium pendulum Sw. (an epiphytic orchid) using light and scanning electron microscopy were described. Anther primordium initiated as a homogenous mass of meristematic cells which developed two thecae, each with a group of archesporial cells of dense cytoplasmic contents. The sporogenous cells of the hypodermal layer formed the anther wall which was 4-5 layered in S. sinensis and 7-layered in C. pendulum. The rare feature of 2-layered endothecium in S. sinensis and a 2-layered tapetum in C. pendulum was reported. Papillate epidermis was observed in C. pendulum. A complete septum of sterile cells in S. sinensis and partial in C. pendulum was observed. Pollen grains were mono-aperturate, reticulate and shed as tetrads in S. sinensis while either monoaperturate or inaperturate, tectate pollen grains and dispersed as hard pollinia in C. pendulum. This is a see-through information for accurate classification and phylogenetic reconstructions of orchid species. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18035 Bangladesh J. Bot. 42(2): 307-314, 2013 (December)